Neurofibromatosis type 1 and cardiac manifestations - Faruk İncecik; Özlem M Hergüner; Sevcan Alınç-erdem; Şakir Altunbaşak (KARE Publishing, 2015)
Objective: Cardiac manifestations of neurofibromatosis type 1 (NF1) may include hypertension, congenital heart disease, and hypertrophic cardiomyopathy. The aim of this study was to evaluate cardiac abnormalities in patients with NF1. Methods: Sixty-five NF1 patients (mean age: 9+-4.48 years) were retrospectively studied. Standard electrocardiography and echocardiography were performed in all patients. Results: Cardiac abnormalities were found in 11 of the 65 patients (15.3%). Five patients had mitral valve regurgitation, 2 patients had secundum atrial septal defect, 1 patient had pulmonary valvular stenosis, 1 patient had ventricular septal defect, 1 patient had tricuspid valve regurgitation, and 1 patient had aortic valve regurgitation. Conclusion: Cardiac abnormalities have potential long-term hemodynamic consequences that justify an early diagnosis. Thus, for any patient with NF1, a cardiologic assessment is mandatory at the time of diagnosis and with regular follow-up intervals.